Antibacterial Activity of Avicennia Mangrove - Yeni Mulyani; Yuniar Mulyani; Aisyah Aisyah (ALCHEMY Jurnal Penelitian Kimia, 2025)
The rise of antibiotic resistance presents a major challenge, reducing the efficacy of conventional antibacterial treatments and necessitating the discovery of novel antimicrobial agents. The use of natural products has played a pivotal role in the development of antibiotics. Specifically, marine organisms, with a notable emphasis on mangroves of the genus Avicennia, have played a crucial role in this process. Avicennia marina, Avicennia officinalis, Avicennia alba, and Avicennia germinans have been found to contain secondary metabolites, including flavonoids, tannins, alkaloids, and terpenoids, which exhibit antibacterial properties against drug-resistant pathogens. The review was conducted based on literature published between 2005 and 2025. These compounds act through diverse mechanisms such as disrupting bacterial cell walls, inhibiting protein synthesis, and interfering with quorum sensing and biofilm formation. Evaluations through disk diffusion, microdilution assay, and biofilm inhibition assays have demonstrated the significant antibacterial activity of Avicennia extracts, suggesting their potential as alternative therapeutics in combating resistant bacteria. Future research should focus on enhancing these bioactive compounds’ bioavailability, stability, and large-scale production while addressing potential toxicity and navigating the complex regulatory requirements for drug approval. The continued exploration of Avicennia-derived compounds may contribute to developing novel antibiotics, offering sustainable solutions to antibiotic resistance.